Time Perception of an Artwork’s Manipulation Is Distorted by Patients With Parkinson’s Disease - Motta, Márcia Regina; Tumas, Vitor; Bueno, José Lino Oliveira (Frontiers in Integrative Neuroscience, 2019)
In artwork appreciation situations, individuals often show altered time perception. We tested the hypothesis that Parkinson’s disease (PD) patients present movement patterns that have an impact on the time perception of artwork manipulation time. We predicted that, compared to healthy controls (HCs), differences in the exploratory behavior of patients would evoke alteration of artwork manipulation time perception. Methods: Ten PD patients and 10 HCs manipulated two reproductions of artwork with different complexity levels from the series “Bichos” by Lygia Clark. Subsequently, participants performed a verbal estimation regarding the temporal duration of their manipulations. The sessions were recorded, and exploratory behavior was analyzed. Results: All participants overestimated the artwork manipulation time. However, PD patients, regardless of the artwork’s level of complexity, showed shorter manipulation time and minor time overestimation compared to the HCs participants. PD patients touched the artworks more often, especially the more complex artworks, than the HCs participants; in contrast, PD patients moved the artworks less often, particularly the less complex artwork. Conclusions: PD patients showed an altered perception of artwork manipulation time. This suggests that exploratory behavior influenced temporal estimation. Besides, it is likely that PD patients had presented a decreased ability to manage attention during the task, which interfered in the cognitive reconstruction of its duration. Considered altogether, these appointments indicate that, as a result of cognitive and motor deficits, PD patients showed impairment in temporal information processing. The exploratory behavior facilitated the understanding of these results and processes in terms of motor-timing operations of the basal ganglia-thalamocortical system.